2018
DOI: 10.1002/2017jd028262
|View full text |Cite
|
Sign up to set email alerts
|

Langley Calibration Analysis of Solar Spectroradiometric Measurements: Spectral Aerosol Optical Thickness Retrievals

Abstract: Aerosol optical thickness (τaer) is a fundamental parameter for analyzing aerosol loading and associated radiative effects. The τaer can constrain many inversion algorithms using passive/active sensor measurements to retrieve other aerosol properties and/or the abundance of trace gases. In the next wave of spectroradiometric observations from geostationary platforms, we envision that a strategically distributed network of robust, well‐calibrated ground‐based spectroradiometers will comprehensively complement s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 62 publications
(86 reference statements)
2
24
0
Order By: Relevance
“…Note that the SMART‐s spectral range covers ozone Chappuis band that also can be used for increasing information content of tropospheric ozone, as well as for its total column retrievals. Jeong et al () reported that well calibrated and maintained SMART‐s instrument offers high‐spectral resolution retrievals of aerosol optical thickness ( τ aer ), which are in excellent agreement with those retrieved from the collocated AERONET measurements at available discrete channels. The spectral τ aer is a key constraint of higher‐order inversion of aerosol microphysical properties (Dubovik & King, ), which are also critical for vertical profile retrievals of aerosols and trace gases.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Note that the SMART‐s spectral range covers ozone Chappuis band that also can be used for increasing information content of tropospheric ozone, as well as for its total column retrievals. Jeong et al () reported that well calibrated and maintained SMART‐s instrument offers high‐spectral resolution retrievals of aerosol optical thickness ( τ aer ), which are in excellent agreement with those retrieved from the collocated AERONET measurements at available discrete channels. The spectral τ aer is a key constraint of higher‐order inversion of aerosol microphysical properties (Dubovik & King, ), which are also critical for vertical profile retrievals of aerosols and trace gases.…”
Section: Introductionmentioning
confidence: 84%
“…Then, the spectral τ aer can be derived by subtracting out the absorption optical thickness of trace gases, associated with TCAs from the previous step, using the total spectral optical thickness. Note that the spectral τ aer retrievals at this step are not affected by the type or vertical distribution of aerosols (Jeong et al, ). Similar to the AERONET protocol, the combination of TCAs of trace gases, spectral τ aer , and almucantar measurements of sky radiance, the column microphysical and optical properties of aerosols are readily retrieved (e.g., Dubovik & King, ).…”
Section: Introductionmentioning
confidence: 99%
“…These two sites are separated by a distance of about 1200 km, a typical synoptic scale, such that the weather at these sites can be quite different, allowing us to study the eclipse-induced 80 surface SW changes under different atmospheric conditions. The ground-based instruments include a thermal-dome-effect-corrected (TDE) pyranometer (Ji and Tsay, 2010), a standard Pandora spectrometer instrument system (PSI) for 280-520 nm wavelength range (Herman et al, 2009) and an extendedrange PSI (PSI-ER) for 280-820 nm wavelength range (Jeong et al, 2018) at both sites. The pyranometer is a broadband radiometer that measures solar radiation reaching Earth's surface with wavelengths approximately from 295 nm to 2800 nm.…”
Section: Ground-based Observation Experiments 75mentioning
confidence: 99%
“…The PSI is capable of obtaining NO2 and ozone total column amounts (for details, see Herman et al, 2009Herman et al, , 2015. The PSI-ER has the capability to retrieve aerosol and cloud optical depths within the given wavelength range (Jeong et al, 2018). Note that cloud optical depth is usually much larger than aerosol optical depth.…”
Section: Ground-based Observation Experiments 75mentioning
confidence: 99%
“…The Langley extrapolation was first used to measure the solar spectrum at the top of the atmosphere (Langley, 1903) 115 and has also been used to measure atmospheric constituents (e.g., Jeong et al, 2018;Toledano et al, 2018;Barreto et al, 2017;Huber et al, 1995;Bhartia et al, 1995). However, the assumption of a constant is often violated due to diurnal variabilities in the atmospheric constituents driven by, e.g., the incident solar radiation, transmittance, circulation, and human activities.…”
Section: The Model-based Minimum-amount Langley Extrapolationmentioning
confidence: 99%